Importance of ultrasonography in follow-up of multiple breast fibroadenomas - Stojanović Ristić, Snežana; Toljić, Branka (General Practice, 2024)
Introduction: Regular ultrasonographic check-upshelp in early detection and follow-up of different diseases.Ultrasonography (US) is of the utmost diagnostic importancefor mammographically „dense breasts“, where glandular tissueis predominant, while in so-called „fat breasts“ it is lessreliable. It is used to determine the solid or cystic nature ofa lesion, often tissue characterization, and the Doppler techniquecould reveal vascularization characteristics of the mass.Fibroadenomas are the most common benign breast tumorsin women of all ages until menopause, with the highest incidencebetween 15 and 25 years of age. The US detects distinctlycircumscribed, rarely round or lobular, hypoechoicmasses with smooth and flat contours, uniform echoes withposterior augmentation, and marginal echo fading.Case report: We presented a female patient aged 21,who had multiple lesions in both breasts (25 lesions in total).Ultrasonographic exams were performed multiple times,in the last 5 years, and magnetic resonance (NMR) was donetwice. Histopathologic verification diagnosed fibroadenomas.The biggest masses were surgically removed four timesin this patient. What are the next steps? Are surgical interventionsneeded again, and if not how should she be followed upin the future? Is the implant insertion eligible for the sake ofesthetic correction?Conclusion: Ultrasonography is a very significant andimportant method of follow-up of breast lesions. Mammographyand magnetic resonance are used as complementarymethods. According to a radiologist’s expert opinions onbreast diseases, ultrasonographic exams every six monthsand NMR may indicate the need for surgical intervention,especially if new
Keywords: ltrasonography; breast; fibroadenoma; young person